The Analysis of Pedagogical Content Knowledge (PCK) at Natural Science Teachers in SMP Negeri 4 Sidoarjo - Mochamad Nashrullah; Septi Budi Sartika; Nur Efendi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze (1) Pedagogical Content Knowledge (PCK) profile of IPA teachers in teaching science in terms of PCK component in pentagon model (2) constraint of PCK science teacher in teaching science. The PCK component consists of five components including: Component K1 (teaching orientation), K2 (knowledge of Curriculum), K3 (knowledge of students), K4 (knowledge of learning strategy) and K5 (knowledge of assessment). The research is a qualitative with phenomenology approach. The subject of the research was a science teacher at SMPN 4 Sidoarjo. Data collection techniques in this study using documentation, observation and interviews. Data analysis phase using Miles and Huberman model. Test the validity of the data used triangulation technique. Based on the research results revealed PCK teacher profile: K1 component is science learning oriented to develop the cognitive, psychomotor and affective aspects of students by applying constructivism learning theory, K2 component that is understanding the curriculum 2013 and apply it to learning but conducted development on objectives, content and learning materials, K3 component: identify that students do not experience misconception and in managing the classroom asking the students who have the advantage to help other students, K4 component is applying discovery learning model with scientific approach 5M (observing, asking, collecting data, associating and creating), K5 component is the assessment of the students covering 3 aspects (cognitive, affective and psychomotor) with assessment methods of quetion and observation, and teachers do not experience PCK constraints in teaching Water Pollution Material. In the next research is expected to reveal three other teacher competencies.